Evaluation of Warm Season Annual Forages for Livestock: Biomass and Cost of Production - J. K. Farney; M. E. Reeb; Z. T. Buessing; K. Malone; G. F. Sassenrath (Kansas Agricultural Experiment Station Research Reports, 2021)
Seventeen warm season annual forage options were evaluated as livestock feed to be grazed, hayed, ensiled, or left as a cover crop. Treatments were planted in mid-May and terminated in late September with one harvest for silage, two hay cuttings, and three grazing rotations. One additional treatment was unharvested to serve as a cover crop. Biomass production and cost to produce final outputs were determined. Even with restricted rainfall during the summer months in 2020, the growth for the chosen forage options was at least 1,500 lb of dry matter (DM) per acre, with the exception of sunflowers that had the lowest biomass production. Biomass production was the greatest for the forages that were left in the field as cover crop, followed by hay, then grazed, with the lowest biomass measured for the silage harvest. Monocultures of grass and sunn hemp produced as much biomass as multi-species blends that included grass or sunn hemp. Adding a high-producing grass species to sunflower and cowpeas increased biomass production compared to the respective monoculture. Regardless of harvest method, monocultures of cowpea and the blend of pearl millet + cowpea cost the most per unit of production. The lowest costs per unit of production for all harvest methods were found in three treatments: a monoculture of sorghum-sudan, the low seeding rate of pearl millet, and the blend of sorghum-sudan + sunn hemp.
Keywords: mono-culture annual forage; multi-species annual forage; cover crop; biomass